Effect of recycled aggregate from concrete waste on concrete compressive strength - Haliza, Mohd Jeffery Ong (2010)
Aggregate is one of the main ingredients in producing concrete. It covers 75% of the total for any one concrete mix. The strength of the concrete produced is dependent on the properties of aggregates used. However, the construction industry is increasingly making higher demands of this material and is feared to accommodate the many requests at one time. With this need other alternatives to prevent this from happening. The study was conducted on recycled aggregate from destroyed concrete. This study aims to investigate the characteristics of recycled aggregate concrete, which consists of various grades of hardened concrete is broken (recycle aggregate). Four different mixtures were produced. Control mixture, used as a reference while other samples containing the ratio of total aggregate content varied between normal aggregate and also "recycle aggregate." Decision analysis found that the characteristics of aggregates used are different than normal aggregate. Control mixture showed better results compared with the mixture of using recycled aggregate. Research shows that more recycled aggregate is used, the compressive. strength of concrete decreases. However, recycled aggregate can be used for structures that do not require a high specification.